Evaluation of the Mechanical Properties of a Novel Hybrid Composite Composed of Rattan and Date Palm Fiber: An Experimental Study - Kharshiduzzaman, Md; Haque, Mohammad Rejaul; Bhuiyan, Md Shahnewaz; Alam, Sabrul; Mashuk, Md; Ahmed, S.K. Nayeem; Afgani, Shahidul Haque; Gafur, M. A. (Advances in polymer technology, 2024)
Numerous studies have examined rattan and date palm fibers separately, but none have combined both fibers in a single composite. This research focuses on creating novel hybrid composites using untreated and treated rattan and date palm fibers. Fibers were treated with 3%, 4%, and 5% NaOH solutions. Fiber diameters were measured microscopically. The NaOH treatment enhanced the tensile strength of the fibers. Untreated rattan, midrib, and spadix stem fibers exhibited tensile strengths of 18, 57, and 37 MPa, respectively. Polyester was used as the matrix, combined with fibers in weight fractions of 70 : 30, 75 : 25, and 80 : 20. All composites were made for 1 : 1 rattan–midrib and 1 : 1 rattan–spadix stem fibers. Composites containing 20% treated rattan–midrib fibers displayed the highest tensile and flexural strengths, measuring 13 and 39 MPa, respectively. Meanwhile, rattan–spadix stem composites achieved the highest tensile strength of 14 MPa at 30% treated fiber loading, and the highest flexural strength of 28.91 MPa at 20% fiber wt.%. Additionally, SEM images of the tensile fracture surfaces revealed voids, cracks, and impurities. The goal was to develop a new composite that provides a low cost, structurally sound, and environmentally friendly strong material suited for industrial, construction, and aviation applications.